Control charts for individual observations of a bivariate Poisson process - Ho, Linda Lee; Branco Costa, Antonio Fernando [UNESP] (Springer London Ltd, 2009)
In this paper, three single-control charts are proposed to monitor individual observations of a bivariate Poisson process. The specified false-alarm risk, their control limits, and ARLs were determined to compare their performances for different types and sizes of shifts. In most of the cases, the single charts presented better performance rather than two separate control charts ( one for each quality characteristic). A numerical example illustrates the proposed control charts.
Keywords: Control charts; Bivariate Poisson distribution; ARL